Inheritance of soybean resistance to Rotylenchulus reniformis - Cardoso,Paulo C. (2014)
Genetic inheritance of soybean resistance to Rotylenchulus reniformis was studied by evaluating the phenotypic reaction of soybean plants to the nematode. The resistant (Forrest and Custer) and susceptible (BR96-25619) soybean cultivars used as parents as well as the F1, F2 and F2:3 derived from their crosses were infested individually with 1,000 eggs and vermiform R. reniformis. About 70 days after the infestation, the nematodes were extracted from the roots and the reproduction factors and the numbers of nematodes per gram of roots were estimated, and data were adjusted for genetic models. Results suggested a predominance of additive genetic effects controlling the nematode resistance reaction. Based on mean and variance genetic models, further genetic gains are expected in the crossing Custer x BR96-25619. The effect of genetic dominance is towards susceptibility. The presence of significant epistasis indicates the existence of at least two genes controlling resistance and that they are interacting. The normal continuous distribution of frequencies of the number of individuals in different classes of resistance indicates that the resistance to the reniform nematode is inherited quantitatively.